METODE EXPERIENTAL LEARNING DALAM PROSES PEMBELAJARAN MENULIS PARAGRAF NARASI BAHASA JERMAN SISWA KELAS XI SMAN 12 SURABAYA - MURIYATIN (LATERNE, 2016)
Writing skills in a foreign language is the most difficult skill in learning. The students have difficulty in finding the ideas to write, especially in Paragraf Narrative writing . One method of learning that can be applied is Experiential Learning Method. This method can be applied upon giving the material in the classroom as well as in the form of paragraph narrative writing exercises to be done individually by pouring what is in his thoughts into an article based on their personal experiences , respectively. The statement of problem in this research is “how the process of learning to write Narrative Paragraphs in German Language using Experiential Learning Method for student in class XI of SMAN 12 Surabaya?”. This study aims “to determine the process of learning to write Narrative Paragraphs in German Language using Experiential Learning Method for student in class XI of SMAN 12 Surabaya”. This study is a qualitative descriptive study and performed a total of 4 meetings . The research instrument is a non-test , the use of instrument is the observation student observation sheet . Observation results of research data and documentation for use Experiental Learning Methods in paragraph narrative writing skills German. The research data is analyzed using qualitative descriptive approach . The number of students in this study is 29 students . During the four times meet sessions, students were given a lesson by using Experiential Learning method. The results showed that the Experiental learning method has been well implemented according in accordance with step stride. The result of the observation showed that the students became more active during the learning process. The students came to like learning German language with Experiental learning method, especially in writing. Student learning outcomes of each meeting has increased, although there are some errors in the writing like writing Articles and placement uppercase. So, it can beconcluded that Experiental learning method can be used as an alternative in learning Germanlanguage, especially in the teaching of writing skills. Keywords : Writing Skills , Naration Paragraph, Experiental Learning method